2020
DOI: 10.1080/09546634.2020.1801975
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-TNF and IL-inhibitors treatments in patients with psoriasis in terms of response to routine laboratory parameter dynamics

Abstract: Background: Biological agent treatments represent a relatively new field and their effects on routine laboratory parameters are not fully known as there has been little research in the area. In our study, we aimed to evaluate the differences between the two main biological treatment groups and their effects on routine laboratory parameters. Methods: Patients were enrolled when they had received treatment for more than six months with biological treatments between January 2013 and April 2020. The available data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
(13 reference statements)
0
25
1
1
Order By: Relevance
“…In the study of An et al, it was found that the NLR value at the 3rd and 6th months of the treatment in patients with psoriasis who received biological agent treatment decreased statistically significantly. However, when four different biological agents (etanercept, adalimumab, infliximab, ustekinumab) were compared, no significant change was found between them in terms of the effect on the NLR value 25 …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the study of An et al, it was found that the NLR value at the 3rd and 6th months of the treatment in patients with psoriasis who received biological agent treatment decreased statistically significantly. However, when four different biological agents (etanercept, adalimumab, infliximab, ustekinumab) were compared, no significant change was found between them in terms of the effect on the NLR value 25 …”
Section: Discussionmentioning
confidence: 94%
“…An et al found that in patients with psoriasis treated with biological agents, the PLR value at the 3rd and 6th months of treatment was statistically significantly decreased. However, when four different biological agents (etanercept, adalimumab, infliximab and ustekinumab) were compared among themselves, no significant change was found in PLR values 25 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Ataseven et al [28] reported a significant decrease in proinflammatory indicators in patients with psoriasis treated with anti-TNF inhibitors compared to patients treated with interleukin antagonists. However, it is not yet evident whether the decrease in sperm production in patients with untreated psoriasis is primarily due to the effect of the disease itself on sperm production, or if it arises from the effect of the accompanying inflammatory status with high levels of proinflammatory cytokines that are tumor necrosis factor alpha, interleukin1 alpha and beta.…”
Section: Discussionmentioning
confidence: 99%